Ethnos oblige : theory and evidence - Zoogah, Baniyelme D. (Emerald Publishing Limited, 2022)
There is nothing wrong with the tribe just as there is nothing wrong with the nation. After all, modern nations are macro-tribes and tribes are micro-nations. So, if there is national obligation then there can be tribal obligation. Ethnos Oblige: Theory and Evidence outlines how these ethnic obligations of individuals manifest and determine positive and negative outcomes to them, their organizations, and societies. Focusing on psychological perspectives and proposing a new theoretical approach to help understand why individuals behave the way they do, both in work and non-work contexts, Ethnos Oblige offers readers a new perspective to reconsider ethnicity. Taking as its primary focus management practices based on extensive empirical evidence from primary and secondary data gathered from across Africa, the book investigates the cultural context through the lens of different ethnic groups, and the lingering effects of colonial legacy as manifested in post-colonial behaviors across differing industrial and cultural sectors. Dr. Zoogah presents revelatory findings on the drivers of ethnic identity and related contingencies, as well as suggestions for organizational implications for employee relations, organization behavior, institutional entrepreneurship and overall business strategy.